Decor Design Sdn Bhd / Roslinda Arifin ... [et al.] - Arifin, Roslinda; Arshad, Nooradila; Samsudin, Asiah; Abd Hamid, Diyana; Mohamed Asrap, Nor Aznim (2001)
Nowadays, many of Bumiputera becomes entrepreneurs because of realizing that business is one field that can guaranty our future. But as entrepreneurs we have to face the risk and we have to work hard to run our business successfully. Our target is to earn profits and to maintain the business as long as possible. We have chosen to open this type of business after we did a research and survey referring to some criteria such as location, target market, and competitors. We have decided to open our business at the location that there is no similar business in operation. Our business is selling piece and wall to wall carpets with various types of patterns and colors. We have many types of imported carpets and there are many choices for customers. DÉCOR DESIGN BHD will start the business on the 1" January 2003.